When Tinder Swiping Gets Challenging: Women’s Narratives of Gender-Based Violence as Shared Through Quora - Sabili, Zivana; Poerwandari, Elizabeth Kristi (Psychological Research on Urban Society, 2023)
Amidst the popular use of Tinder in urban society, the decision whether or not to date someone tends to be made quickly based on a photo and a short profile description. Simple as it may seem, there are moments when swiping gets challenging, especially for women. Tinder has a notorious reputation when it comes to gender-based violence. Unfortunately, despite the significant increase in online dating apps usage during the COVID-19 pandemic, this phenomenon is still highly underresearched. In this qualitative netnographic research, we explore Tinder sexual harassment narratives uploaded by women in Quora. Through judgment sampling, 15 answers from 7 questions posted by Quora users and 12 comments were analyzed. Criteria of inclusion for answers are as follows: Answers should (1) contain personal account on violence and/or harassment related to Tinder-use, (2) be written by women, (3) indicate that the perpetrator is male. Data were analyzed through thematic analysis. Four main themes emerged: the forms of gender-based violence experienced by women while dating men from Tinder, women’s feelings after experiencing gender-based violence perpetrated by their Tinder dates, women’s responses after experiencing gender-based violence from their Tinder dates, and responses from other Quora users after reading women’s stories on gender-based violence experienced through Tinder.